Knowledge, Attitude and Practice (KAP) study for thalassemia: a cross-sectional study at BRAC University, Bangladesh - Mim, Afsana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.